International Tourism Policy and Development: Indian Tourism Policy - Mehrad, Dr. Aida; Sharma, Kaushal; Patil, Rishab Madan; Wilson, Wilfin Mangalan; Moustansir, Adnane (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
India is one of the worldwide tourist goals. The current study focused on it in the context of tourism policy and its industry, which is rapidly growing, particularly in Delhi and Mumbai. The rapid growth of India's tourism industry is affected by several factors, including the country's high economic growth rate over the past decade and the fact that it is now one of the more affordable destinations for foreign tourists. Additionally, several significant challenges are associated with developing the Indian tourism industry. To address these challenges and ensure that India's tourism industry continues to increase in the years to come, the government has introduced several new tourism policies aimed at improving the infrastructure available in the country and making it easier for tourists to come and visit. These policies include introducing a dedicated high-speed rail link between Delhi and Mumbai, developing a new visa policy for foreign visitors, and simplifying the process for acquiring permits for filming or photography in popular tourist attractions nationwide. Overall, these policies represent a significant step in developing the Indian tourism industry and will go a long way towards guaranteeing that the country remains a popular destination for tourists worldwide for many years; this study focused on it deeply based on earlier investigations.